Combating digital piracy in China and its unintended side effects - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
Research shows a reduction in online piracy in China’s digital publishing sector boosted creative production but also reduced writers’ efforts in engaging with readers